2021
DOI: 10.3389/fendo.2021.641888
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Study of Immune System Associated Genes in Case of Type-2 Diabetes With Insulin Action and Resistance, and/or Obesity

Abstract: Type-2 diabetes and obesity are among the leading human diseases and highly complex in terms of diagnostic and therapeutic approaches and are among the most frequent and highly complex and heterogeneous in nature. Based on epidemiological evidence, it is known that the patients suffering from obesity are considered to be at a significantly higher risk of type-2 diabetes. There are several pieces of evidence that support the hypothesis that these diseases interlinked and obesity may aggravate the risk(s) of typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…MATLAB coding was also used for figure plotting and analysis. The primary idea of the FunCoup network database is that it predicts four different forms of functional coupling or links, such as protein complexes, protein-protein physical interactions, metabolic, and signaling pathways ( Alexeyenko and Sonnhammer 2009 ; Bajrai et al, 2021b ; Bajrai et al, 2021a ; Eldakhakhny et al, 2021 ; Kamal et al, 2020 ; Mobashir et al, 2012 ; Mobashir et al, 2014 ; Warsi et al, 2020 ). Swiss-dock ( http://www.swissdock.ch ) ( Grosdidier et al, 2011 ; Kumar et al, 2020 ) was utilized for docking analysis, with PubChem ( https://pubchem.ncbi.nlm.nih.gov/ ), UniProt ( https://www.uniprot.org/ ), and swiss-model ( https://swissmodel.expasy.org ) as supporting databases ( Kumar et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…MATLAB coding was also used for figure plotting and analysis. The primary idea of the FunCoup network database is that it predicts four different forms of functional coupling or links, such as protein complexes, protein-protein physical interactions, metabolic, and signaling pathways ( Alexeyenko and Sonnhammer 2009 ; Bajrai et al, 2021b ; Bajrai et al, 2021a ; Eldakhakhny et al, 2021 ; Kamal et al, 2020 ; Mobashir et al, 2012 ; Mobashir et al, 2014 ; Warsi et al, 2020 ). Swiss-dock ( http://www.swissdock.ch ) ( Grosdidier et al, 2011 ; Kumar et al, 2020 ) was utilized for docking analysis, with PubChem ( https://pubchem.ncbi.nlm.nih.gov/ ), UniProt ( https://www.uniprot.org/ ), and swiss-model ( https://swissmodel.expasy.org ) as supporting databases ( Kumar et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Still, they are in different directions. To simplify and bring many directional works in one study, we have applied an integrated approach from data acquisition to analysis and network-level understanding (63,69,83,84). From this study, there are many concluding points in terms of the MARK4 interactors, drug-target identifications, mutational profiling, functional aberrations, and clinical relevance, which are quite straightforward from data analysis to presentation, potential drug-target prediction, and conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…network database to predict four different forms of functional coupling or links, such as protein complexes, protein-protein physical interactions, metabolic, and signaling pathways(51,61,64,65,(67)(68)(69)(70). Swiss-dock was utilized for docking analysis (http://www.swissdock.ch)(18,48), with PubChem (https:// pubchem.ncbi.nlm.nih.gov), UniProt (https://www.uniprot.org/ ), and swiss-model (https://swissmodel.expasy.org) as supporting databases…”
mentioning
confidence: 99%
“…36 37 Notably, SPNS1 has recently been considered as a core component of T cell receptor signalling. 38 A slew of studies have shown that TRIM10 and TRIM27 were involved in several inflammation processes. [39][40][41] TRIM10 exhibited a lower expression in patients with systemic lupus erythematosus than in healthy individuals, which negatively induced the IFN/JAK/STAT signalling pathway through impacting the interaction between IFNAR1 and TYK2.…”
Section: Discussionmentioning
confidence: 99%